(untitled) (The Pakistan Development Review, 1967)
The Sociology of Development is an ambitious attempt at developing a model of Asian societies which will explain succinctly the reasons why Asian nations have not developed economically, why sociologists working in underdeveloped areas are not effective in their attempts to expedite social change, why economists can do nothing about economic development, and among other questions why foreign aid is of no value to economic development. Indeed, Professor Jacobs’ "shotgun" approach to the sociology of development touches briefly on so many aspects of economic development that one can only wish that an attempt had been made to equip the gun with a full choke. Briefly, the book may be seen to consist of three parts. The first part consists of a single introductory chapter which attempts to do several things within the space of 18 pages. First, it is argued that Iran is selected as only a case study of the entire problem of economic development in Asia, yet neither in this chapter nor in subsequent chapters is an extended attempt made to draw similarities between Iran and other countries in Asia. The most important reason for the selection of Iran, a Middle Eastern nation, seems to be that the author spent two years, 1959 to 1961, in Iran.